2008
DOI: 10.1177/0146167208328329
|View full text |Cite
|
Sign up to set email alerts
|

What We Regret Most Are Lost Opportunities: A Theory of Regret Intensity

Abstract: A recent theory (Roese & Summerville, 2005) has suggested that regret is intensified by perceptions of future opportunity. In this work, however, it is proposed that feelings of regret are more likely elicited by perceptions of lost opportunity: People regret outcomes that could have been changed in the past but can no longer be changed and for which people experience low psychological closure. Consistent with the lost opportunity principle, Study 1 revealed that regretted experiences in the most commonly regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 63 publications
7
109
1
Order By: Relevance
“…In the younger group, regret intensity was not strongly associated with wellbeing. These results were replicated in a second study, which also showed that among older adults, having future goals reliably predicted reduced levels of regret intensity and higher levels of life satisfaction, which as Beike, Markman and Karadogan (2009) point out, is at odds with Roese and Summerville"s (2005) opportunity principle. Stewart and Vanderwater (1999) showed that regret-inspired life changes also bring contentment.…”
Section: The Impact Of Regretmentioning
confidence: 73%
See 2 more Smart Citations
“…In the younger group, regret intensity was not strongly associated with wellbeing. These results were replicated in a second study, which also showed that among older adults, having future goals reliably predicted reduced levels of regret intensity and higher levels of life satisfaction, which as Beike, Markman and Karadogan (2009) point out, is at odds with Roese and Summerville"s (2005) opportunity principle. Stewart and Vanderwater (1999) showed that regret-inspired life changes also bring contentment.…”
Section: The Impact Of Regretmentioning
confidence: 73%
“…Beike, Markman and Karadogan (2009) challenge the basic premise of the opportunity principle and argue that regret stems not from realising that an opportunity is still viable, but from recognising that it is irredeemably lost. They point to the fact that education, the most regretted life domain in Roese and Summerville"s (2005) meta-analysis, would not represent a source of future opportunity for many of the participants surveyed, some of whom were elderly adults.…”
Section: Who Experiences Regret What Do People Regret and Why?mentioning
confidence: 99%
See 1 more Smart Citation
“…According to this notion, adolescents expressing high levels of PA may experience 'action-orientation', movement forward and attainment/ achievement thereby operating with "locomotion" orientation. Beike et al [50] have shown that the tendency to regret actions is to a large extent a 'non-action whereas actions, 'in the long run', provide more positive feelings than passivity. As a self-regulatory strategy, high levels of "locomotion", based on coping behavior rather than inaction, may have contribute to elevated PA in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Robinson et al [52] have postulated that NA functions as a 'defense' mechanism by either provoking a passive state wherein watchfulness and reticence are prioritized or, alternatively, that individuals applying high levels of "assessment" invest more effort on ruminating prior to choice and these deliberations induce worry and other feelings linked to NA. Individuals identified through behavioral inaction tend to express more regret [53] and experience a higher degree of NA [54] through inaction than if they had attempted, even persisted, towards a goal [50,55]. Excessive hesitancy may accompany the pursuance of an "assessment" approach to choice and decision-making leading to inaction and reducing the quality of preferences and decisions [56].…”
Section: Discussionmentioning
confidence: 99%